2023
DOI: 10.1371/journal.ppat.1011152
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus transcription factor ZfpA regulates hyphal development and alters susceptibility to antifungals and neutrophil killing during infection

Abstract: Hyphal growth is essential for host colonization during Aspergillus infection. The transcription factor ZfpA regulates A. fumigatus hyphal development including branching, septation, and cell wall composition. However, how ZfpA affects fungal growth and susceptibility to host immunity during infection has not been investigated. Here, we use the larval zebrafish-Aspergillus infection model and primary human neutrophils to probe how ZfpA affects A. fumigatus pathogenesis and response to antifungal drugs in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
1
8
3
Order By: Relevance
“…Bearing in mind that the C2H2 transcription factor ZfpA is required for the hyperbranching and chitin responses to 5,8-diHODE 20 and 8-HODE (Supplementary Fig. 7 ) as well as being involved in tolerance to caspofungin 23 , we thought it likely that ZfpA could be required for 5,8-diHODE protection of A. fumigatus against the fungicidal activity of echinocandins. We performed germling lysis experiments with WT, ∆ zfpA , and OE:: zfpA strains in both Af293 and CEA10 genetic backgrounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind that the C2H2 transcription factor ZfpA is required for the hyperbranching and chitin responses to 5,8-diHODE 20 and 8-HODE (Supplementary Fig. 7 ) as well as being involved in tolerance to caspofungin 23 , we thought it likely that ZfpA could be required for 5,8-diHODE protection of A. fumigatus against the fungicidal activity of echinocandins. We performed germling lysis experiments with WT, ∆ zfpA , and OE:: zfpA strains in both Af293 and CEA10 genetic backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…We found that A. fumigatus response to 5,8-diHODE requires the transcription factor ZfpA and that overexpression of ZfpA phenocopies treatment with 5,8-diHODE thus also resulting in hyperbranched, highly septate hyphae enriched in chitin 20 . Furthermore, deletion of ZfpA renders A. fumigatus more sensitive to caspofungin both in vitro and in vivo whereas its overexpression mediates protection against the antifungal drug 20 , 22 , 23 . Published RNA-sequencing data shows both the ppoA and zfpA transcripts are upregulated under caspofungin treatment 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the intriguing observation that inhibition of glycogenolysis promotes neutrophil migration towards chemoattractant, we further assessed the impact of nutrient utilization shift on neutrophil migration and its downstream impact in pathogen control in the setting of fungal infection with Aspergillus fumigatus 37 -- Neutrophils play a significant role in controlling the growth of the invasive pathogen A. fumigatus, and coordinated swarming towards the pathogen enables effective fungal control. In this experiment, to avoid the direct impact of GPi treatment on A. fumigatus , we pre-treated primary human neutrophils with GPi for 1 hour, then removed the GPi and co-incubated neutrophils with fungal germlings in fresh culture media.…”
Section: Resultsmentioning
confidence: 99%
“…For mycelial RNA, A. fumigatus wild type, ∆zfpA, and OE::zfpA conidia were inoculated at 10 6 spores per mL in liquid glucose minimal media and incubated at 37˚C shaking at 250 RPM overnight (60). For each sample, the total tissue was combined from two 50mL cultures flash frozen and lyophilized.…”
Section: Rnaseq Extraction From a Fumigatus Zfpa Mutantsmentioning
confidence: 99%